Workshop Introducing The Internet of Things For Teachers and Students Ar Ridho Al-Qur'an Educational - Ari Kurniawan; Dwi Sidik Permana; Rahmat Jaya; Filda Angellia; Natalia Ervianti; Dyah Utami Dewi; Muhammad Febriansyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The scientific approach to computer technology is a support in all fields of education and at all levels of education. One of them is about the Internet of Things or what is usually called IoT. At the Al-Qur'an Education Park (TPA), computer technology knowledge and the like are a support for learning, but this knowledge cannot be directly obtained considering that there are no scientific resources such as teachers who are experts in this field, high implementation costs, concerns about security and data privacy, resistance to change, and inadequate technological infrastructure. By overcoming these challenges through the right approach and adequate support, implementing IoT in TPA can bring significant benefits in improving the quality of education and students' readiness to face an increasingly digital future. Based on these points, lecturers from the Faculty of Computer Science, Kosgoro 1957 Institute of Business and Informatics, designed Community Service activities (PKM) with the main aim of implementing the Internet of Things (IoT) in the Al-Qur'an Education Park (TPA) in order to improve the quality of education in an innovative and efficient way. By utilizing IoT, this activity is expected to make a real contribution to the transformation of education in TPA. This activity was carried out in the form of a workshop, including providing intensive workshops to teachers and students about the basics of IoT, the use of IoT devices, and other technologies related to IoT. Apart from that, there was also an outreach session for teachers and students about the benefits and importance of IoT in life. The application of IoT in TPA not only improves the quality of learning, but also has broad implications, such as empowering teachers in using technology, as well as increasing awareness of the importance of being wise in using technology. This PKM activity can also be a model for other educational institutions in adopting technology to improve the quality and effectiveness of education.